Lexical and Phonological Levelling in the Speech of Qassimi Arabic Speakers - Alhumaid, Anfal (International Journal of Language and Literary Studies, 2024)
This study on linguistic levelling in the speech of Qassimi Arabic speakers found that there are six distinct aspects of phonological levelling present in the dialect, coupled with a plethora of examples on lexical levelling among two groups. Qassimi Arabic speakers who reside in Qassim region and have lived there their entire lives, and Qassimi Arabic speakers who have resided in different Saudi regions most of their adult lives. Findings indicate that women are more likely to engage in levelling, and those with less education, and resident in Qassim are less likely to engage in levelling. Dialect changes occurred in nearly 2 of 3 participants and were due to the mixing of cultures and growing urbanisation. The results of the study are in line with other literature indicating that speakers of Qassimi Arabic engage in spontaneous levelling of their dialect for prosocial motives, for reasons having to do with ease of use and convenience. The study made meaningful contributions in explicating the specific aspects of phonological and lexical levelling with respect to the Qassimi Arabic dialect and to the influences of variables such as gender, age, gender, and region.